Analysis of the Implementation of JELITA Information System using Technology Acceptance Model (TAM) at Salatiga City Health Office - Binbaryas Isna Aski Koreri Rumabar; Andeka Rocky Tanaamah; Hanna Prillysca Chernovita (Sistemasi: Jurnal Sistem Informasi, 2023)
In the current era of globalization, with the development of information technology which is growing rapidly, it becomes a necessity for a government. Information Technology is an electronic device that functions to process data, store information, and send and process data. Sophisticated technology can have data that is relevant, accurate, and timely so that it can be used in various fields of the world of digitalization. The application of information technology in government has an important role, where for each use it requires the existence of a supporting technology to facilitate digital-based work. One of the government agencies is using the Healthy City Information Window Information System (JELITA), namely the Salatiga City Health Office, a government agency engaged in the Health sector that adopts an Information System to create a healthy district or city. The research was conducted using the Technology Acceptance Model (TAM) analysis with a qualitative approach method, directly conducting interviews with Salatiga City Health Service Employees in the Public Health Sector. The results of this research are that the JELITA Information System plays an important role in assisting work activities in ranking healthy cities, namely adding important documents that are done online or digitally without having to do it manually.